“Attractive to Strangers and Instructive to Students.” The McCullochs’ 19th Century Bird Collection in Dalhousie College - Mills, Eric (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2013)
Thomas McCulloch, Presbyterian minister and educator, founder of Pictou Academy, first President of Dalhousie College 1838-1843, established a museum in Pictou, NS, by 1828, including a bird collection. To McCulloch, the order of the natural world instilled in students principles of a liberal education and a model of society. His first collections were sold, but when McCulloch came to Dalhousie in 1838 he started a new collection, hoping to make it the basis of a provincial museum. In this he was aided by his son Thomas, who had been trained as a taxidermist. The younger McCulloch kept and expanded the collection until his death, after which it passed to Dalhousie College. The current McCulloch Collection, mainly the work of Thomas McCulloch junior, seems to exemplify purposes and practices of 19th century natural history. But research shows that the collection has a hybrid origin and must be viewed with great caution as an historical artifact. This is a case study in the difficulty of interpreting 19th century natural history collections without careful examination of their history.